Sản phẩm và dịch vụ thông tin khoa học và công nghệ phục vụ Chương trình quốc gia phát triển công nghệ cao đến năm 2020 tại Cục Thông tin khoa học và công nghệ quốc gia - Trân, Thị Hải Yến (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Discuss the role of S&T information products and services for the National Program of Hi-tech Development until 2020; investigates the present situation of serving with information and satisfying information need of this Program and sets forth S&T information products and services to enhance its effectiveness.